Numerical investigation on the behavior of combining open-channel flow - Nor Azni Shahari; Nor Arif Husaini Norwaza; Iskandar Shah Mohd Zawawi; Nurisha Adrina Mohd Kamarul; Aimi Said (Institute of Advanced Engineering and Science, 2021)
Open-channel flow is known as fluid flow with an open atmospheric surface. It has become an important issue especially when measuring the flow rate and depth of water as part of environmental management schemes. Many efforts have been made by the previous researchers to investigate the behavior of water flow. However, most studies on water flow have only been carried out in a straight prismatic main channel, either in a trapezoidal and rectangular type of channel section with lateral branch of angle of 90o. In this study, the general equations of combining open-channel flow for trapezoidal and V-shaped channels are modified in the form of nonlinear polynomial equations. The proposed equations are solved using Newton-Raphson procedure to determine the upstream flow depth. All the computations and analysis of the behavior of water flow depth influenced by Froude number and flow rate ratio are performed using graphical user interface, which is designed in MATLAB software. Comparative analysis shows that the modified equations agree well with the experimental data as reported in the literature. The trapezoidal channel demonstrates the highest value of flow depth as the Froude number and flow rate ratio increase; thus, it has potential to avoid water overflow.